ANALISIS KOMUNIKASI MATEMATIS DITINJAU DARI TINGKAT KEMAMPUAN SISWA SMK PADA MATA PELAJARAN MATEMATIKA: Array - Widodo, An Nur Ami; Astuti, Wiki Windi (Jurnal Dialektika Program Studi Pendidikan Matematika, 2019)
This research aims to determine the achievement of mathematical communication that has not been met by students of class X SMK Semesta Bumiayu in solving trigonometry problems based on NCTM's mathematical communication indicators in terms of the level of students' abilities. This type of research is qualitative with a case research approach. Subject selection criteria are based on students' mathematical communication skills, namely high, medium, and low mathematical communication skills. The subjects of this research were students of Pharmacy X grade 1 of Universe Bumiayu which consisted of 9 subjects namely 3 subjects with high mathematical communication skills, 3 subjects with moderate mathematical communication skills, and 3 subjects with low mathematical communication skills. Data collection is done by interview and test techniques, then the data is analyzed using mathematical communication indicators. Then triangulation of sources is done to obtain valid research data. This research ultimately resulted in the conclusion that there were still a number of indicators that had not been fulfilled.